Women and leadership in university management and research (Ágora de Heterodoxias, 2020)
Assuming our female leadership in these challenging times, through research, management and dissemination implies confronting subtle and not so subtle barriers in Latin America. In addition, one way to do it is by accepting the challenge of women's collaboration and alliance supporting other women. In this case, it is not a feminist action, rather what is postulated is a cooperative action in which it is understood that one way to conquer spaces, which have been denied from the patriarchal culture, is by recognizing ourselves as that other legitimately creative, intelligent and versatile. Without ageism and without disqualifying ourselves because it is part of a culture with which, as women, we have contributed to preserve
Keywords: Women; leadership; university management and research